Approximation by Nörlund Means of Hexagonal Fourier Series (Analysis in Theory and Applications, 2017)
Let $f$ be an $H$−periodic Hölder continuous function of two real variables.The error $||f −N_n(p;f)||$ is estimated in the uniform norm and in the Hölder norm,where $p=(p_k)^∞_{k=0}$ is a nonincreasing sequence of positive numbers and $N_n(p; f)$ is the $n\rm{th}$ Nörlund mean of hexagonal Fourier series of $f$ with respect to $p=(p_k)^∞_{k=0}$.
Keywords: Hexagonal Fourier series; Hölder class; Nörlund mean.